PENGARUH VARIASI WARNA PLAT KOLEKTOR SURYA TERHADAP KINERJA PEMANAS AIR TENAGA SURYA - Harizalni SE; Aris Zainul Muttaqin; Santoso Mulyadi (ROTOR, 2014)
Solar water heater  is a device  that heats water using  solar collectors as a heat absorber of  solar  radiation  that is  transmitted  to  the pipe containing water  . In  this research, comparative performance  testing of solar water heating to solar collector plate color variations . Variations of color used is black ( black ) no. ( 39 ) with the brand of quick drying formula zuper spray acrylic spray paint , red ( red signal ) no. ( 23 ) with rj LONDON acrylic paint brand epoxy spray paint  , and blue  ( blue  fluorescent  ) no.  ( 1004) with rj LONDON acrylic paint brand spray paint epoxy Data collection was performed by  taking data every 30 minutes  for 3 hours are 9:00 to 12:00 pm at the clock and the test performed 3 times on different days . Data taken from the study include inlet and outlet water temperature collectors , and the temperature of the water in the tank , which is then carried out data processing  to determine  the  flow rate  ,  the density of water  ,  the water  temperature difference in and out collector  ( ÄT  )  ,  the performance of solar water heaters  ( q  )  , and processing  the data graphically . The results of the study of each color plate solar collector plate showed that the color black has the highest absorption compared with red and blue , because the color black has emissivity close to 1 ( objects that are almost black)  is a  transmitter as well as a good heat absorber. Kata kunci: Kolektor, emisivitas, warna plat, air